Influence of altitude on the structure, floristic composition and carbon of Choco forests - Torres-Torres, Jhon Jerley (2021)
Introduction: Despite the wide biodiversity found in the Chocó, little has been documented on the influence of altitude on floristic composition, structure, diversity, biomass and tree carbon. Objective: To evaluate the influence of altitude on the floristic composition, structure and carbon stored in forests of the Quibdó (QDO)-Carmen de Atrato (CA) altitudinal gradient in the biogeographic Choco.  Methods: Eighteen plots (20×20m) were established in a gradient of 100-1700m altitude between QDO and CA, Choco. The floristic composition was analyzed using Ward's method and a simple linear regression was performed to observe the relationship between altitude and structural and biomass variables. Diversity was estimated using Shannon's and Simpson's indices. Biomass was calculated using an allometric equation developed for this forest type. Carbon was estimated with a carbon fraction of 0,5. Results: A total of 773 individuals were found, comprising 90 species and 33 botanical families. The sites at lower altitudes presented greater richness. The families with the highest number of tree species were: Fabaceae, Malvaceae, Lauraceae and Clusiaceae. Ward's analysis allowed separating the sites into two statistically different groups (p ˂ 0,05), the first of lower altitude dominated by the species Iryanthera tricornis Ducke, Brosimum utile (Kunth) Pittier. and Pithecellobium sp. and the second of higher altitude dominated by Aniba puchury-minor (Mart.) Mez. At the density level, few differences were observed between sites, while the basal area decreased with increasing altitude. For the variables species richness, basal area, diversity and biomass, negative relationships and correlations were obtained with altitude, while for density this was positive. On average, carbon stored in aboveground biomass was 68.28Mg h-1 for the QDO- CA altitudinal gradient (100-1700masl), which decreases as altitude increases and differs statistically among the sites sampled (p ˂ 0,05). Conclusion: Altitude exerts a strong negative influence on the floristic composition (species richness and floristic turnover), structure (basal area and Importance Value Index), biomass and carbon of the ecosystems studied.